Protection of Metal Artifacts with the Formation of Metal–Oxalates Complexes by Beauveria bassiana - Joseph, Edith; Cario, Sylvie; Simon, Anaële; Wörle, Marie; Mazzeo, Rocco; Junier, Pilar; Job, Daniel (Frontiers in Microbiology, 2012)
Several fungi present high tolerance to toxic metals and some are able to transform metals into metal-oxalate complexes. In this study, the ability of Beauveria bassiana to produce copper oxalates was evaluated in vitro. Growth performance was tested on various copper-containing media. B. bassiana proved highly resistant to copper, tolerating concentrations of up to 20 g.L-1, and precipitating copper oxalates on all media tested. Chromatographic analyses showed that this species produced oxalic acid as sole metal chelator. The production of metal-oxalates can be used in the restoration and conservation of archaeological and modern metal artefacts. The production of copper-oxalates was confirmed directly using metallic pieces (both archaeological and modern). The conversion of corrosion products into copper oxalates was demonstrated as well. In order to assess whether the capability of B. bassiana to produce metal-oxalates could be applied to other metals, iron and silver were tested as well. Iron appears to be directly sequestered in the wall of the fungal hyphae forming oxalates and probably goethite. However, the formation of a homogeneous layer on the object is not yet optimal. Silver nitrate was extracellularly reduced into nanoparticles of elemental silver by an unknown mechanism. The production of copper oxalates is immediately applicable for the conservation of copper-based artefacts. For iron and silver this is not yet the case. However, the vast ability of B. bassiana to transform toxic metals using different immobilization mechanisms seems to offer considerable possibilities for industrial applications, such as the bioremediation of contaminated soils or the green synthesis of chemicals.